91 METASTATIC MALIGNANT MELANOMA PRESENTING AS MASSIVE LOWER GASTROINTESTINAL BLEEDING. (1st March 2007) - Sircar, P.; Godkar, D.; Balachandran, J.; Niranjan, S.
Abstract : Introduction: Malignant melanoma represents 1 to 3% of cancers in the United States, and its prevalence is steadily increasing. Metastatic melanoma of the small bowel is a pathologic entity that is infrequently reported, and antemortem diagnosis is made in only 1.5 to 4.4% of all patients with melanoma. Gastrointestinal metastases may manifest as mucosal or submucosal masses, serosal implants, or carcinomatosis. They arise more commonly in the mesentery or distal small bowel than the proximal gastrointestinal tract or colon. Rarely are these lesions symptomatic; sometimes patients present with pain, obstruction, and occult or overt gastrointestinal bleeding. We present an unusual case of metastatic malignant melanoma of the second part of the duodenum presenting as life-threatening gastrointestinal hemorrhage. Case Report: A 53-year-old Russian lady came to the emergency room after an episode of syncope. She also complained of progressively worsening shortness of breath and fatigue for a few months. Her past medical history was remarkable for a history of malignant melanoma of the skin diagnosed 3 years ago, for which she had received excisional surgery and had remained free of recurrence for 3 years. Physical examination was significant for extreme pallor and multiple pigmented skin lesions of variable sizes on the trunk and back. She was neurologically intact, and the abdomen was benign, but rectal examination revealed soft dark stool, strongly guaiac positive, without masses or lesions. Initial laboratory work revealed a hemoglobin of 5.7g/dL, with microcytic red cell indices (MCV 62.1 fl). Her electrolytes, liver function tests, and renal function tests were all within normal limits. Chest radiography revealed multiple parenchymal lesions bilaterally, and CT of the brain with intravenous contrast showed multiple lesions in the brain parenchyma without mass effect. The patient was transfused two units of packed red cells and underwent endoscopic studies to evaluate the cause of her profound anemia and was found to have a mass lesion at the second part of the duodenum. She underwent duodenoscopy with biopsy of the lesion, which revealed metastatic malignant melanoma (immunohistochemical stains showing S-100 and melan-A positive). Also, biopsy from the skin lesions at the back revealed malignant melanoma arising from compound nevus, with level III invasion, and a tumor thickness of 0.8 mm. The patient did not bleed any further from her duodenal lesion but was not deemed to be a candidate for therapeutic resection of the lesion, owing to her widely metastatic disease. The patient underwent palliative radiotherapy for her brain lesions and was put on prophylactic steroids, but she went through a rapidly downhill course and succumbed to her disease a few weeks later. Discussion: Malignant melanoma has the propensity to metastasize widely. Most reported cases of gastrointestinal metastases are those of mucosal or submucosal masses, serosal implants, or carcinomatosis, the most common form being multiple submucosal implants growing intraluminally to cause intestinal obstruction. However, many of these lesions can also ulcerate, resulting in occult or overt gastrointestinal bleeding. Although patients with gastrointestinal tract metastases from melanoma carry a dismal prognosis, many such patients can have palliation of symptoms by surgical resection with minimum morbidity and mortality. It is therefore important for clinicians to make an accurate and timely diagnosis of the cause of gastrointestinal bleeding in such patients to prevent rapidly fatal outcomes.